Impact of Prosopis (mesquite) invasion and clearing on ecosystem structure, function and agricultural productivity in semi-arid Nama Karoo rangeland, South Africa - Ndhlovu, Thabisisani (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScConEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2011.